Application of sawdust concrete in construction - Kropidłowska, Oliwia (Budownictwo i Architektura / Civil and Architectural Engineering, 2022)
Sawdust concrete is a type of lightweight concrete in which some of the mineral aggregate is replaced by sawdust - a by-product of wood processing. It is not a new material, but its potential is not utilised to its full degree. Taking into account the most important advantages of sawdust concrete - lower density and greater thermal and acoustic insulation than ordinary concrete - it is worth to consider the possibilities of its usage in construction wider than currently . In order to present the properties of sawdust concrete, the review of contemporary technical literature has been performed. For the production of sawdust concretes mineralized sawdust from various types of trees, ordinary cements, mineral aggregates and water, are used. The usage of additives and admixtures is also allowed. The properties of the finished sawdust concrete are mainly influenced by the proportion of its components, especially the amount of fine aggregates replaced by sawdust. The construction products made of sawdust concrete are characterized by a low coefficient of thermal conductivity λ and soundproofing properties. In bending tests, a simply supported sawdust concrete beam behaves similar to a regular concrete beam, cracks first appear in the tension zone. Tensile strength, compressive strength and Young's modulus of sawdust concrete products depend on the proportion of components and the method of sawdust preparation before applying in the sawdust concrete-mix. Compared to ordinary concrete, the obtained values for sawdust concrete are lower, but partially fall within the ranges for the lower classes of ordinary concrete. There are several possible applications of sawdust concrete in construction. One of the perspectives is to use it to build walls in buildings that require soundproofing between rooms, or to replace wood with it when renovating old buildings. However, further tests of sawdust concrete are needed in terms of the most favourable composition for its mechanical properties, and to define the standards according to which sawdust concrete elements should be produced.